Three-dimensional finite element modeling of intermediate crack debonding in fiber-reinforced-polymer-strengthened reinforced concrete beams. Issue 10 (July 2019) - Xie, En-Li; Zhou, Chao-Yang; Yu, Ya-Nan; Liu, Jun
Intermediate crack debonding is a common failure mode of reinforced concrete beams strengthened in flexure with an externally bonded laminate (sheet or plate) of fiber-reinforced polymer. Many finite element models have been developed to predict this failure mode. Research shows that the accurate modeling of interfaces between concrete and either internal steel or external fiber-reinforced polymer reinforcements is very important. This article presents a three-dimensional finite element model based on the smeared crack approach for predicting intermediate crack debonding failure of fiber-reinforced-polymer-strengthened reinforced concrete beams (including preloaded beams). In this model steel-to-concrete and fiber-reinforced-polymer-to-concrete interfaces are more expediently modeled. The finite element results agree well with experimental results on crack patterns, fiber-reinforced polymer strain distribution, and the variation of strain and deflection with load. This model can also simulate the fiber-reinforced polymer debonding process of the beam and the response of the residual beam after the fiber-reinforced polymer reinforcement has separated from the reinforced concrete beam. In addition, parameters' analyses are further conducted to find the differences between the two-dimensional and three-dimensional models. Simulations of fiber-reinforced polymer-plated slabs or beams with additional anchors are mostly three-dimensional problems, and their focus is also on intermediate crack debonding. This model can be used to simulate fiber-reinforced-polymer-plated slabs or beams with additional anchors such as U-jacket strips or mechanically fastened fiber-reinforced polymer strengthening systems in future research.